Analisis Kemampuan Penggunaan Teknologi Informasi Mahasiswa dalam Pembelajaran Matematika di Era Pandemi Covid-19 - Sihotang, S F; Ramadhani, R (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2021)
The Covid-19 pandemic had a major impact on various sectors, including the education sector. All schools and colleges in almost all countries affected by Covid-19 have implemented online learning. After being run for one-year, online learning conditions cannot be considered ideal because there are still various obstacles faced, especially in terms of the students' ability to use information technology. Facts that I found on my campus, there are still many students who find it difficult in terms of applications used and in terms of methods or processes of online learning. Thus, this study aims to analyze the influence of students' ability to use information technology variables on the difficulties experienced by students during online learning with E-learning media assistance in terms of applications used and in terms of learning methods or processes online during mathematics learning in the Covid-19 pandemic outbreak. The research method used in this study is structural equation modelling (SEM) analysis, to test the hypothesis. After conducting the research, the results obtained stated that the most positive and significant impact on students' ability to use information technology, namely the applications used during online learning variable compared to the online learning method or process variables themselves during mathematics learning in the Covid-19 pandemic outbreak.